Association between leukocyte telomere length and sex by quantile regression analysis - Gutierrez-Rodrigues, Fernanda; Alves-Paiva, Raquel M.; Scatena, Natália F.; Martinez, Edson Z.; Scheucher, Priscila S.; Calado, Rodrigo T. (Hematology, Transfusion and Cell Therapy, 2022)
Telomere length (TL) is a biomarker of cellular proliferative history. In healthy individuals, leukocyte TL shortens with age and associates with the lifespan of men and women. However, most of studies had used linear regression models to address the association of the TL attrition, aging and sex. We evaluated the association between the TL, aging and sex in a cohort of 180 healthy subjects by quantile regression. The TL of nucleated blood cells was measured by fluorescent in situ hypridization (flow-FISH) in a cohort of 89 men, 81 women, and 10 umbilical cord samples. The results were validated by quantitative polymerase chain reaction (qPCR) and compared to a linear regression analysis. By quantile regression, telomere dynamics slightly differed between sexes with aging: women had longer telomeres at birth and slower attrition rate than men until the sixth decade of life; after that, TL eroded faster and became shorter than that in men. These differences were not observed by linear regression analysis, as the overall telomere attrition rates in women and men were similar (42 pb per year, p < 0.0001 vs. 45 pb kb per year, p < 0.0001). Also, qPCR did not recapitulate flow-FISH findings, as the telomere dynamics by qPCR followed a linear model. The quantile regression analysis accurately reproduced a third-order polynomial TL attrition rate in both women and men, but it depended on the technique applied to measure TL. The Flow-FISH reproduced the expected telomere dynamics through life and, differently from the qPCR, was able to detect the subtle TL variations associated with sex and aging.